Strategi Konten dan Customer Engagement dalam Komunikasi Pemasaran Digital Industri Air Conditioning di Indonesia - Deta Anggraini (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Digital technology has transformed corporate marketing communication from a one-way model into a more interactive, social-media-based exchange. In the Air Conditioning (AC) industry, social media functions as a strategic instrument for relationship building, brand-image reinforcement, and Customer Engagement enhancement. This study examines the content strategies, Customer Engagement patterns, and platform effectiveness employed by Daikin, Gree, and Midea in digital marketing communication in Indonesia. A descriptive qualitative approach was applied through 14-day digital observation of the official Instagram, Facebook, and TikTok accounts of the three brands, yielding 81 posts as the unit of analysis. Data were analyzed using the Miles and Huberman interactive model comprising data reduction, data display, and conclusion drawing. The results indicate that TikTok is the most effective platform for generating audience Engagement owing to its interactive, short-video format. Product content (38.3%) and branding content (35.8%) dominate the brands’ communication strategies, whereas educational and interactive content remain limited. Gree achieved the highest Engagement by integrating educational, entertaining, and interactive elements, demonstrating that follower count alone does not determine Engagement quality. These findings reinforce Content Marketing Theory, Customer Engagement Theory, and Computer-Mediated Communication (CMC) by showing that content quality, platform characteristics, and communicative interactivity jointly drive audience Engagement. This study contributes to digital marketing communication research in the durable-goods sector in Indonesia.